Digital Literature as a Convergence Ecosystem: A Digital Humanities Perspective on Contemporary Literary Practices in Indonesia - Bambang Riyanto; Rosnidar Ain (Talenta Publisher, 2026)
The rapid development of digital technologies has fundamentally transformed the ways literature is produced, circulated, and consumed. This article examines digital literature in Indonesia as a form of convergence culture in which literary texts, digital platforms, audiences, and creative industries interact within an increasingly interconnected ecosystem. Drawing on Henry Jenkins’ (2006) concept of convergence culture and informed by perspectives from digital humanities, the study investigates how contemporary literary practices are reshaped through digital media environments. This research employs a descriptive qualitative approach based on literature review and the analysis of empirical evidence drawn from the digital literary practices of four influential Indonesian figures: Fiersa Besari, Raditya Dika, Tere Liye, and Tsana (Rintik Sedu). The analysis focuses on three dimensions: the transformation of literary forms, audience participation, and the convergence of cultural industries. The findings reveal that digital literature in Indonesia has evolved beyond the mere digitization of literary texts into a dynamic cultural ecosystem. Literary works increasingly circulate across multiple media formats, including social media, music, film, podcasts, streaming platforms, and community-based events. At the same time, audience participation has become a crucial source of literary visibility, legitimacy, and sustainability, shifting authority from traditional literary institutions toward networked digital communities. Furthermore, literary production is increasingly integrated with broader creative industries, generating new models of cultural production, distribution, and monetization. The study argues that the most significant transformation in contemporary Indonesian literature is the emergence of a convergence ecosystem in which texts, audiences, platforms, and industries continuously shape one another. While digital humanities provide an important analytical perspective for understanding the relationship between literature and technology, convergence culture offers a more effective framework for explaining the structural changes occurring in contemporary literary production. These developments also raise critical concerns regarding algorithmic visibility, commercialization, and the fragmentation of literary meaning within digital environments